Pengaruh Efektivitas Promosi Media Sosial Instagram untuk Meningkatkan Kesadaran Merek dan Niat Beli Konsumen : Studi Kasus: Bistro Balige, Sumatera Utara - Claudia Cahyani Sinaga; Mariana Simanjuntak (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of Instagram social media promotion effectiveness on brand awareness and consumer purchase intention, with a case study on Bistro Balige, North Sumatra. Using a quantitative approach with a survey method, this research involved 70 respondents selected through purposive sampling. Data were analyzed using the Structural Equation Model (SEM) with the assistance of SmartPLS 4.0. The results show that the effectiveness of Instagram promotion has a positive and significant effect on brand awareness and consumer purchase intention. However, brand awareness does not have a significant influence on purchase intention. These findings provide valuable insights for culinary businesses in tourist areas like Lake Toba in optimizing their digital promotion strategies.